Prevalence and Antibiotic Resistance of Non-typhoidal Salmonella Isolated from Raw Chicken Carcasses of Commercial Broilers and Spent Hens in Tai’an, China - Li, Song; Zhou, Yufa; Miao, Zengmin (Frontiers in Microbiology, 2017)
The present study was aimed to determine the prevalence and characteristics of Salmonella isolated from meat samples of commercial broilers (CB) and spent hens (SH). Between March and June 2016, 200 retail raw chicken carcasses (100 from CB and 100 from SH) were obtained from local supermarkets in Tai'an city of China, and Salmonella isolates were then analyzed for antibiotic resistance, serotype, β-lactamase genes, and the presence of class 1 integron. Forty Salmonella strains were obtained in this study (CB: 21/100, 21％; SH: 19/100, 19％). Three serotypes were identified in 40 Salmonella, and S. Enteritidis (CB: 15/21, 71.4％; SH: 10/19, 52.6％) was the dominant serotype, followed by S. Typhimurium (CB: 4/21, 19％; SH: 6/19, 31.6％) and S. Derby (CB: 2/21, 9.5％; SH: 3/19, 15.8％). Among 21 Salmonella isolated from CB, high antibiotic resistance rates were found for ampicillin (20/21, 95.2％), nalidixic acid (18/21, 85.7％), cefotaxime (17/21, 81％), and tetracycline (13/21, 61.9％); class 1 integron was observed in 7 isolates (7/21, 33.3％), and gene cassettes included an empty integron (0.15kb, n=1), aadA2 (1.2kb, n=3), drfA1-aadA1 (1.4kb, n=1), and drfA17-aadA5 (1.7kb, n=2); blaTEM-1 was the dominant β-lactamase gene (21/21, 100％), followed by blaCTX-M-55 (7/21, 33.3％). Among 19 Salmonella isolated from SH, high antibiotic resistance rates were found for nalidixic acid (19/19, 100％), tetracycline (19/19, 100％), ampicillin (18/19, 94.7％), and ciprofloxacin (13/19, 68.4％); class 1 integron was observed in 2 isolates (2/19, 10.5％), and gene cassettes included drfA17-aadA5 (1.7kb, n=1) and drfA1-aadA1(1.4kb, n=1); blaTEM-1 was the dominant β-lactamase gene (19/19, 100％), followed by blaCTX-M-55 (2/19, 10.5％) and blaCMY-2 (1/19, 5.3％). Collectively, antibiotic-resistant Salmonella can be widely detected in retail raw chicken carcasses of CB and SH, and therefore can pose a serious risk to public health.